Technological Learning and technological capability building of new media organizations in the Philippines in exploiting data science' promise and potential - Asturias, Robert Lue R. (University of the Philippines Diliman, 2017)
Today, there is about 2.5 quintillion bytes of data that are created. This huge number of data are coming from digital pictures, videos, posts to social media sites, intelligent sensors, purchase transaction records, cellphone GPS signals, and others (Zicari, Big Data: Challenges and Opportunities). This is known as Big Data. Big Data is usually defined as any data sets whose size in beyond the ability of typical database software tools to capture, store, manage and analyze. This is a new platform of technology incorporated on a huge realm of data science. Data science or sometimes called data driven science is an interdisciplinary field where applications of scientific methodologies, processes and systems, were integrated to be able to get insights and patterns from huge amount of structured or unstructured data. This is one of the new emerging technologies that is expected to shape the future technology in the nearest time. Currently, organizations and industries abroad have already started using data science and big data to leverage their sales and growth and become more competitive on their arena. The value that can be gained from data science and big data are not limited to creating transparencies, discovering needs, exposing variabilities, improving performance, segmenting customers and replacing or supporting human decisions - making with automated algorithms. Or in other words, data science and big data are innovating and ready to cannibalize existing technology to produce new business models, products and services. The focus of this paper is to determine the technological capability and technological learning of new media organizations in utilizing data science. Journalists practicing data journalism or data driven journalism had been very active not only our neighboring countries but in the Philippines as well. Integration of data science and big data can be helpful to enrich the capability of the Philippine media to level-up and produce a new breed of journalism that is supported by massive amount of data and information. To bridge further gaps between the desired levels of technological capability of new media organizations in the Philippines, barriers in adopting the data science technology had been identified. SWOT and PESTEL analyses had been presented in order to describe the environmental landscape of this technology. Recommendations that will possibly help boost and accelerate the adoption of data science in journalism were discussed on the later part of the paper. Venn diagrams were also used in this project to evaluate the technology and describe the characteristics of data science journalisim.